2020
DOI: 10.1021/acssensors.0c01980
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Analytical Platform with Enzyme-Modulated Dynamic Range for the Simultaneous Colorimetric Detection of Sweat Volume and Sweat Biomarkers

Abstract: In this manuscript, we introduce a wearable analytical platform that simultaneously measures the concentration of sweat lactate and sample volume. It contains two sensors entirely made of filter paper that can be easily affixed on the skin with medical-grade tape. The lactate biosensor features a unique signal modulation mechanism that enables fine-tuning the dynamic range. It consists of adding a competitive enzyme inhibitor in different reservoirs. Thanks to this, it is possible to choose between a very low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 40 publications
2
43
0
1
Order By: Relevance
“…Vaquer et al developed a sweat volume colorimetric platform made of filter paper and simply attached to the skin with tape based on colorimetry. [162] As illustrated in Figure 11a,b, dyes are stored in a reservoir, which were carried through the paper strip by the absorbed sensible sweat from the user. Then, the SSV was estimated by additionally gauging the length of the stained paper.…”
Section: Filter Papermentioning
confidence: 99%
See 2 more Smart Citations
“…Vaquer et al developed a sweat volume colorimetric platform made of filter paper and simply attached to the skin with tape based on colorimetry. [162] As illustrated in Figure 11a,b, dyes are stored in a reservoir, which were carried through the paper strip by the absorbed sensible sweat from the user. Then, the SSV was estimated by additionally gauging the length of the stained paper.…”
Section: Filter Papermentioning
confidence: 99%
“…As the sponge absorbed sensible sweat, the resonance frequency of the SLMD becomes inversely proportional to the water content in the sponge owing to the change in the dielectric property (Figure 12b,c). As a result, such device design enabled wireless quan- [162] Copyright 2020, American Chemical Society. c) Conceptual illustration and photograph of a finger-shaped wearable colorimetric patch.…”
Section: Spongementioning
confidence: 99%
See 1 more Smart Citation
“…Section 2.1.2) have been used in many wearable devices. [133][134][135][136][137][138] Color changes can be detected by the Figure 6. Electrochemical sensors for wearable applications.…”
Section: Colorimetric Sensorsmentioning
confidence: 99%
“…[139] Colorimetric sensors can be fabricated on different wearable substrates, such as paper, [140] hydrogel, [141] fiber, [142] fabric, [143] and yarn. [133,134] Wearable colorimetric devices include onskin platform, [135,144,145] smart band, [143] wristband, [146] contact lenses, [138] T-shirt, [133] etc., and are usually used to detect human sweat, [136,137,143] tears, [138] VOCs, [134] UV, [147] etc. Kim et al [134] demonstrated an eye-readable and wearable H 2 S sensing platform based on colorimetric dye-loaded nanofiber yarn, which could be incorporated into a worker's garment as a visual indicator; and was adequate for inexpensive mass-production (Figure 7A).…”
Section: (9 Of 20)mentioning
confidence: 99%